2022
DOI: 10.3390/su14041990
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of the COVID-19 Crisis on the Hungarian Employees

Abstract: The economic crisis in the wake of the coronavirus epidemic is affecting the lives, jobs and incomes of a lot of people. Certain sectors of the economy have come to a standstill or stalled for a time, causing many to lose their jobs and be forced to pursue other career options than originally planned. The COVID-19 pandemic caused a deep economic crisis that caused workers to feel insecure, which also had a negative impact on the lives and characteristics of individuals at work. In the course of our research, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…There was a strong relationship between the reduction of the number of Hungarian small and medium-sized businesses and the sense of insecurity felt by employees. Thus, based on the results, it can be concluded that the coronavirus crisis had a negative impact on people's lives due to work-related problems (Karacsony, Krupánszki, Antalik, 2022) and the Turkish real estate market (Tanrıvermiş, 2020).…”
Section: Literature Studiesmentioning
confidence: 99%
“…There was a strong relationship between the reduction of the number of Hungarian small and medium-sized businesses and the sense of insecurity felt by employees. Thus, based on the results, it can be concluded that the coronavirus crisis had a negative impact on people's lives due to work-related problems (Karacsony, Krupánszki, Antalik, 2022) and the Turkish real estate market (Tanrıvermiş, 2020).…”
Section: Literature Studiesmentioning
confidence: 99%
“…Specifically, balancing work and personal responsibilities simultaneously results in greater stress and anxiety as a result of overload. Teleworking has the potential to solve these few main issues by providing several benefits [21], but at the same time, its disadvantages are not insignificant, such as psychological disturbances such as anxiety, depression, and stress, and physical illnesses such as work-related musculoskeletal problems [22].…”
Section: B Work From Home and Job Satisfactionmentioning
confidence: 99%